Kontribusi Dewan Pengawas Syariah Terhadap Kepatuhan Prinsip Syari’ah Pada Lembaga Finansial Technology Syari’ah - Hadi, Wildan; Duhriah; Wira, Ahmad; Hendra, Testru (el-Jizya: Jurnal Ekonomi Islam, 2025)
This study aims to examine the Contribution of the Sharia Supervisory Board (SSB) in ensuring compliance with sharia principles in sharia fintech institutions in Indonesia, while identifying various problems faced. The method used is a literature study with a secondary data analysis approach sourced from scientific articles, journals, and previous research. The results of the study indicate that the SSB plays a crucial role in ensuring sharia compliance, through periodic supervision, implementation of DSN-MUI fatwas, and development of sharia-compliant products and services. However, this study found a number of challenges, including the weak special supervisory mechanism for sharia fintech and the continued violation of sharia principles on several platforms such as Investree, Dana Syariah, and Peer to Peer Lending Syariah. Therefore, this study recommends strengthening the capacity of the SSB, improving regulations, and increasing cooperation between the SSB and related authorities in order to minimize sharia violations. Thus, this study makes an important contribution to strengthening the sharia supervisory system and supporting the sustainable growth of sharia fintech in Indonesia.